PENGARUH BOARD COMPOSITION, MANAGEMENT OWNERSHIP DAN BANK SIZE TERHADAP PROFITABILITAS BANK PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2014 - Syarif, Firman; Zebua, Yolanda Yosephine (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2015)
This research is aimed to investigate the effect of board composition which consists of commissioners and independent commissioners, management ownership, and bank size on bank profitability in banking companies listed in Indonesia Stock Exchange (IDX) during the period of study 2011-2014. This research is a hypothesis testing research. The population of this research is all of the banking companies listed in Indonesia Stock Exchange (IDX) during the period of 2011-2014. The sampling method used is purposive sampling. The data used is secondary data and obtained from the Indonesia Stock Exchange (IDX) website. The research variables consists of bank profitability as dependent variable which is measured by Return On Asset (ROA). Independent variables are board composition, management ownership and bank size. Board composition consists of commissioners and independent commissioners. Commissioners is measured by total member of board of commissioners and independent commissioners is measured by total member of independent commissioners divided by total member of board of commissioners. Management ownership is measured by total stock of management ownership divided by all the total stock of company. Bank size is measured by logaritma natural of total asset from each banking companies. The analysis technique is multiple linear regression. The result show that partially variables of commissioners, independent commissioners and management ownership has no effect to the bank profitability in banking companies, while bank size has effect to the bank profitability in banking companies. Simultaneously, the results show that the variables of commissioners, independent commissioners, management ownership and bank size has influenced to the bank profitability in banking companies.